EFFECT OF COW MANURE BOKASHI FERTILIZER AND SOLID FERTILIZER APPLICATION ON GROWTH AND YIELD OF EGGPLANT (Solanum melongena) IN POT MADE FROM STEM OF OIL PALM PLANTS - Beni Rianto; Cik Zulia; Elfin Efendi (Universitas Asahan, 2018)
This research was conducted in the research garden Faculty of Agriculture University of Asahan, Kisaran Naga Village, Kisaran Barat Subdistrict, Asahan District in March to May 2017. The experiment was arranged in Randomized Complete Block Design with two factors and three replication. The first factor is 3 degree of cow faces bokashi fertilizer application that is F1 = 10 ton/ha (1 kg/plot), F2 = 20 ton /ha (2 kg/plot), F3 = 30 ton/ha (3 kg/plot). Second factor is the solid fertilizer application that is S0 = 0 ton/ha (control), S1 = 10 ton/ha (1 kg/plot), S2 = 20 ton/ha (2 kg/plot). Parameters were observed is hight plant (cm), production per plant (g), production per plot (kg). The result of the research showed that the cow faces bokashi fertilizer have effect on production per sampel about 1.984,45 g and production per plot about 7,44 kg. Solid fertilizer have effect on production per sampel about 2046,63 g and production per plot about 7,69 kg. No interaction of the cow faces bokashi fertilizer and solid fertilizer on growth and yield of eggplant.